2012
DOI: 10.1158/1541-7786.mcr-12-0349
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor Cell Invasion and Dissemination In Vivo by an Aptamer That Inhibits Urokinase-type Plasminogen Activator through a Novel Multifunctional Mechanism

Abstract: Data accumulated over the latest two decades have established that the serine protease urokinase-type plasminogen activator (uPA) is a potential therapeutic target in cancer. When designing inhibitors of the proteolytic activity of serine proteases, obtaining sufficient specificity is problematic since the topology of the proteases’ active sites are highly similar. In an effort to generate highly specific uPA inhibitors with new inhibitory modalities, we isolated uPA-binding RNA aptamers by screening a library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Several strategies to inhibit either CAF activation or CAF-derived factors (e.g. HGF, uPA, CXCL12/SDF1) have been applied in preclinical studies of cancer therapies and the results have shown efficacy in the inhibition of tumor growth and invasion [111][112][113][114][115][116]. Similarly, several immunotherapeutic approaches have been developed to target immune cells that infiltrate the tumor.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 99%
“…Several strategies to inhibit either CAF activation or CAF-derived factors (e.g. HGF, uPA, CXCL12/SDF1) have been applied in preclinical studies of cancer therapies and the results have shown efficacy in the inhibition of tumor growth and invasion [111][112][113][114][115][116]. Similarly, several immunotherapeutic approaches have been developed to target immune cells that infiltrate the tumor.…”
Section: Molecular Network In the Tumor Microenvironmentmentioning
confidence: 99%
“…This effect was suggested to be caused by either the large electronegativity of the aptamer or steric hindrance of access to a key contact surface, and not by an allosteric effect, since catalytic activity toward small substrates (active site integrity) was unaffected by aptamer binding. Another example of extensive shielding of protein surfaces is provided by uPA ‐binding aptamers . These aptamers are able to interfere with protein‐natural ligand interactions in domains separate from the aptamer binding domain.…”
Section: Aptamer‐mediated Perturbation Of Protein Structure and Functionmentioning
confidence: 99%
“…42 However, aptamers binding to the serine protease domain of uPA could be identified by selection against this domain alone. 43 High-throughput sequencing of SELEX pools from a selection with plasminogen activator inhibitor-1 (PAI-1) demonstrated that aptamers binding outside the hot spot site were rare in the pool but that they could be identified easily when selecting with PAI-1 in complex with a natural ligand covering the hot spot site. 44 Hence, the nature of certain protein areas may be particularly well suited for aptamer binding, providing the aptamers binding there with an unexpected large selective advantage.…”
Section: Existence Of Dominant Aptamer Binding Sites On Protein Surfacesmentioning
confidence: 99%
“…A novel class of viral nanoparticles enabled the visualization of newly formed vasculature in expanding tumors (Leong et al, ) and monitoring of targeted‐delivery to the tumor in the CAM (Cho et al, ). This approach to evaluating cancer as a comprehensive (micro)environment is increasingly becoming the standard approach to investigate both the physiology of tumors, the molecular mechanisms that drive them, and therapies that can intervene (Botkjaer et al, ).…”
Section: The Chick As a Model For Cancer Biologymentioning
confidence: 99%
“…Imaging tumor vascular dynamics in the CAM is faster, easier, and less expensive than in mammals, promoting its utility for screening drugs or new designs for drug carriers and potential targeting agents. Current research is testing a variety of targeting strategies that might be used in conjunction with drug carriers to target them more specifically to cancer cells (Bobek et al, ; Zijlstra et al, ; Botkjaer et al, ; Busch et al, ; Fein and Egeblad, ).…”
Section: The Chick As a Model For Cancer Biologymentioning
confidence: 99%